Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd008298
|View full text |Cite
|
Sign up to set email alerts
|

Physical health care monitoring for people with serious mental illness

Abstract: Background Current guidance suggests that we should monitor the physical health of people with serious mental illness and there has been a significant financial investment over recent years to provide this. Objectives To assess the effectiveness of physical health monitoring as a means of reducing morbidity, mortality and reduction in quality of life in people with serious mental illness. Search methods We searched the Cochrane Schizophrenia Group Trials Register (October 2009) which is based on regular search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…There are no evidence-based models of care for providing integrated psychiatric and medical care for these older adults in ambulatory, inpatient, or long-term care settings. (40, 41) Research is needed to better design systems of care to deliver high-quality efficient care to this population across the continuum of care. (40)…”
Section: Discussionmentioning
confidence: 99%
“…There are no evidence-based models of care for providing integrated psychiatric and medical care for these older adults in ambulatory, inpatient, or long-term care settings. (40, 41) Research is needed to better design systems of care to deliver high-quality efficient care to this population across the continuum of care. (40)…”
Section: Discussionmentioning
confidence: 99%
“…However they have less access to medical care, poorer quality of care, and preventative health checks are less commonly completed in both primary and secondary care compared with the general population [15-17]. The nature of their mental illness may also affect their motivation as many individuals may be not ready to change their lifestyle [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A recently published systematic review of the physical health intervention literature [15] concluded that mental health nurses were well-placed to address health behaviours in mental health patients and that specific interventions can result in significant improvements in both health behaviours and physical health outcomes. Although there is currently a lack of evidence from randomised controlled trials [16] the results from less methodologically robust studies suggest that “well-being” initiatives may result in improved patient outcomes [17,18]. …”
Section: Introductionmentioning
confidence: 99%